Dissecting the phenotypic diversity of Ethiopian barley (Hordeum vulgare L.) genotypes through variance components and multivariate analysis - Abeje Belay, Gizie (Acta agriculturae Slovenica, 2025)
Exploring the genetic diversity of barley germplasm conserved in the gene bank is critical for climate-resilient breeding. This study explored the phenotypic diversity and associations of 10 quantitative agro-morphological traits among 229 Ethiopian barley genotypes to identify desirable traits and promising accessions. The experiment was conducted at Holeta Agricultural Research Center in 2023 using an augmented design. The result of the analysis of variance revealed significant variation among the studied genotypes. A significant variabil-ity and wide range of mean performance were observed for the studied traits. Key traits like heading and maturity, grain filling period, 1000-kernel mass, kernel number per spike, and productive tillers were the most discriminating traits contributing to the highest variability (46.9 %). Cluster analysis identified three major trait-specific clusters. Grain yield exhibits a moderate correlation with plant height and kernel number per spike. High phenotypic and genotypic coefficients of variation were obtained for grain yield, productive tillers, kernel number per spike, and spikelet per spike. In addition, high heritability and genetic advance were observed for days to heading, productive tillers, spike length, kernel number and spikelet per spike, and grain yield suggesting selective breeding for these traits is likely to be effective for crop improvement programs.
Keywords: augmented RCBD; barley; characterization; conservation; genetic variability; genetska spremenljivost; izboljšani bločni poskus; ječmen; multivariate; multivaritna analiza; ohranjevanje; ovrednotenje